How to raise a feminist son : motherhood, masculinity, and the making of my family - Jha, Sonora (Sasquatch Books, 2021)
"This book is both an incredibly moving mother-son love story told in personal essays, and a parenting manual with concrete advice and actionable takeaways for feminists of all stripes hoping to dismantle toxic masculinity, one sweet boy at a time"--